Measuring Contextual Impact of Maintenance on Machinery Capacity Utilization and Environment - Ting, C.H; M. I., Shahidul; S. T., Syed Shazali; A., Yassin (ENCON 2013, 2013)
Degree of production machineries capacity utilization is directly impacting on production performance and capacity utilization depends on machineries health; indeed, machinery health is positively associated with maintenance. In this context, this research aims to develop an empirical model to estimate impact of maintenance on machineries capacity utilization. The proposed framework is a hybrid model composed of engineering concept in maintenance and econometrics. Production inputs such as product demand, machinery maintenance and labour directly involved with production have used to estimate machinery utilization. Output elasticity has used to measure impacts of inputs to machinery capacity utilization. Results reveal that developed model is quite suitable to estimate capacity utilization of production machinery. Study reports that machinery capacity utilization is 70% with output elasticity of demand 0.72; while maintenance activity creates a negative impact on capacity utilization with output elasticity 0.065. On the hand, findings report that poor maintenance contributes to increase wastage which negatively associated with environment quality. Potential of the developed model is to generate information on production behaviour useful for optimizing production performance despite information lack in model on capacity loss due to working environment and market pressure.